Peak impact accelerations during track and treadmill running - Bigelow, E. M. R.; Elvin, N. G.; Elvin, A. A.; Arnoczky, S. (Journal of Applied Biomechanics, 2013)
To determine whether peak vertical and horizontal impact accelerations were different while running on a track or on a treadmill, 12 healthy subjects (average age 32.8 ± 9.8 y), were fitted with a novel, wireless accelerometer capable of recording triaxial acceleration over time. The accelerometer was attached to a custom-made acrylic plate and secured at the level of the L5 vertebra via a tight fitting triathlon belt. Each subject ran 4 miles on a synthetic, indoor track at a self-selected pace and accelerations were recorded on three perpendicular axes. Seven days later, the subjects ran 4 miles on a treadmill set at the individual runner`s average pace on the track and the peak vertical and horizontal impact magnitudes between the track and treadmill were compared. There was no difference (P = .52) in the average peak vertical impact accelerations between the track and treadmill over the 4 mile run. However, peak horizontal impact accelerations were greater (P = .0012) on the track when compared with the treadmill. This study demonstrated the feasibility for long-term impact accelerations monitoring using a novel wireless accelerometer.